Where to go? High-skilled individuals' regional preferences - Sabrina Jeworrek; Matthias Brachert (Halle Institute for Economic Research (IWH), 2022)
We conduct a discrete choice experiment to investigate how the location of a firm in a rural or urban region affects job attractiveness and contributes to the spatial sorting of university students and graduates. We characterize the attractiveness of a location based on several dimensions (social life, public infrastructure, connectivity) and combine this information with an urban or rural attribution. We also vary job design as well as contractual characteristics of the job. We find that job offers from companies in rural areas are generally considered less attractive. This is true regardless of the attractiveness of the region. The negative perception is particularly pronounced among persons with urban origin and singles. These persons rate job offers from rural regions significantly worse. In contrast, high-skilled individuals who originate from rural areas as well as individuals with partners and kids have no specific preference for jobs in urban or rural areas.
urn:nbn:de:gbv:3:2-923255
Keywords: J61; R12; R23; R58; 330; discrete choice experiment; job characteristics; locational preferences; rural-urban divide